Mucocele in lower lip as a result of trauma - Deepak Chauhan; Seema Thakur; Kalpana Verma; Ashish Justa (Indian Journal of Dental Sciences, 2021)
Mucocele is a common salivary gland disorder that can appear on the dorsal surface of the tongue, lacrimal sac, paranasal sinuses, and oral cavity. Mucocele results in alteration of the minor salivary glands due to a mucous accumulation causing limited swelling. Two histological types of mucoceles exist, namely extravasation and retention. Lower lip is the most common site of occurrence of these lesions in the oral cavity and the most probable cause is trauma or habits of lip biting. This report presented a 6½-year-old female child patient having mucocele on the inner side of her lower lip due to fall while playing, which resulted difficulty in mastication and speech. Treatment performed was conventional surgical excision followed by removal of the minor salivary glands.